Alice Rue evades the truth - Zipps, Emily (The Dial Press, 2025)
"Alice Rue has never spoken to her longtime crush Nolan Altman, but when she saves his life one night in their office building, the EMTs tell his family that Alice is Nolan's girlfriend. She wants to set the record straight, but Nolan's in a coma, and if the family feels comforted by the idea of Nolan having his "girlfriend" by his side for what might be his last moments, isn't it kinder to go along with it? At least for now? After all, the Altmans are impossibly nice and supportive, and there's something about Nolan's sister, Van, that makes Alice feel more seen and understood than she has in years. The local news names her a hero. Her boss finally starts treating her well. Alice even starts to remember what it's like to have a family. She knows it's wrong to lie, but it's easy to convince herself that she's doing the right thing by evading the truth. What she can't avoid, however, is her growing chemistry with Van. Alice must decide if she can unravel this tangle of lies in order to salvage her chances with the woman who just may be the love of her life-especially if Nolan wakes up. Warm, witty, and full of heart, this debut romcom is a love story for pessimists who secretly hope for their own happily ever after."-- Provided by publisher.